Association between Human Body Composition and Periodontal Disease. (2nd November 2011) - Salekzamani, Yagoub; Shirmohammadi, Adileh; Rahbar, Mohammad; Shakouri, Seyed-kazem; Nayebi, Farough
Abstract : Obesity in humans might increase the risk of periodontitis. The aim of the present study was to examine the relationship between body composition of males and their periodontal status. AS total of 150 males (aged 30–60) were selected: 31 were periodontally healthy, 45 had gingivitis, 39 had initial periodontitis, and 35 suffered from established periodontitis. BMI (body mass index), WC (waist circumference), and body composition parameters (consisting of body water, body fat, and skeletal muscle and bone mass) were measured. After adjusting for age, history of diabetes, smoking, physical activity status, and socioeconomic status, statistically significant correlations were found between periodontitis and BMI, WC, and body composition. There was only a statistically significant difference between the periodontal health and established periodontitis; that is, periodontal disease in mild forms (gingivitis) and initial periodontitis do not influence these variables (BMI, WC, and body composition parameters) and only the severe form of the disease influences the variables. These data suggest that there is a considerable association between severe forms of periodontal disease in males and their body composition, but this preliminary finding needs to be confirmed in more extensive studies.